Evaluation of drug treatment awareness among caregivers and patients of chronic kidney disease: unexplored determinant in patient care - Tripathi, Raakhi K.; Pilliwaer, Chailtali; Gajbhiye, Snehalata; Bhilwade, Sujeet K.; Jamale, Tukaram (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Chronic kidney disease (CKD) patients are prescribed multiple drugs to slow disease progression and prevent complications mandating adherence to therapy. Lack of awareness about drug treatment is one of the contributors to nonadherence. Hence the study was conducted to explore the awareness of patients and caregivers towards CKD treatment. Methods: The study was a cross sectional questionnaire-based study conducted among 300 CKD patients (150 dialysis/150 non-dialysis) and 100 caregivers (50 of dialysis / 50 of non-dialysis patients) attending nephrology OPD at a tertiary care hospital.Patient /caregiver awareness about drug treatment was assessed usinga prevalidated drug awareness questionnaire (8 items). The items were scored as correct response=2, no response=0 and incomplete response = -1, accounting the total awareness score as +20 to - 6 Results: The mean awareness score of patients / caregivers was 8.16±3.41 and 8.3±1.6 respectively. Majority (>70%) patients/ caregivers gave accurate responses for the items -specifying number of medicines, medication frequency and regular intake of drugs but awareness regarding action plan for skipped (27% patients, 11% caregivers) or missed doses (22% patients, 15% caregivers) and adverse effects (17% patients, 5% caregivers) was poor. Patients/ caregivers belonging to dialysis group had statistically better awareness then non-dialysis group. Conclusions: Patient /caregiver awareness regarding drug treatment is less than 50% with strikingly low awareness about dose regimen, adverse effects, action plan for missed doses and co morbidities. Patient education programs to reinforce and retain this knowledge need to be implemented in CKD patients.